THE STUDENTS’ PERCEPTIONS ON STUDENT-TEACHER CLOSENESS IN LEARNING ENGLISH AT PBI UMY - Lutvi Anita Purwanto (PBI 15 UMY 08, 2015)
*8 This research discusses all aspects related to student-teacher closeness in learning English at PBI UMY. Closeness between the students and teachers is needed on the learning process, but there are some pros and cons by the existence of closeness between the students and teachers in learning process. Then the researcher wants to know the type of closeness between the students and teachers, to examine the factors influencing the closeness between the students and teachers, to investigate the impacts of closeness between the students and teachers in PBI UMY. The data collection method employed in this study was interviewed. Seven students in English education department of UMY batch 2010 participated in this study. They invited to attend interview session. They interviewed one by one. Each participant was recorded for analysis. All the students reported that they have a closeness relationship to their teachers. Physical closeness and emotional closeness are the category from the students’ explanation on their closeness relationship. It was influenced by four factors; those are student characteristic, teacher’s characteristic, student-teacher characteristic, and present of study. The student-teacher closeness relationship also really impacted to the students and also to the learning English process at PBI UMY.